(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Neutron radiography (NR) technique has been adopted to study water absorption behavior of single layer tiles made of India and Pakistani raw materials, obtained from Concord Real Estate & Building Products, Shalna, Gazipur, Dhaka, Bangladesh. Measurements were made to study the water absorption behavior of the tiles at different immersion time within the range of 24 hours using conventional NR technique. A series of neutron radiographs of these tiles have been taken at dry and wet condition to observe the water absorption behavior. The optical density differences between the film background and at different reference positions of the radiographic images of the dry and wet samples were measured. In the work it was observed that the water absorption in tiles of Indian origin is less than the other ones. Thus the former one seems better to use for construction purpose. Key words: Neutron radiography; Homogeneity; Water absorption behavior DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8107 Bangladesh J. Sci. Ind. Res. 46(1), 53-58, 2011